To find the solution of the equation 11-4x = -9, you need to isolate the variable x.
First, subtract 11 from both sides of the equation:
11 - 11 - 4x = -9 - 11
-4x = -20
Next, divide both sides of the equation by -4:
(-4x)/-4 = (-20)/-4
x = 5
Therefore, the solution to the equation 11-4x = -9 is x = 5.
what is the solution of this equation 11-4x = -9
7 answers
what is the solution of this equation 2/5x + 4 = 1/5
To find the solution of the equation (2/5)x + 4 = 1/5, you need to isolate the variable x.
First, subtract 4 from both sides of the equation:
(2/5)x + 4 - 4 = 1/5 - 4
(2/5)x = 1/5 - 20/5
(2/5)x = -19/5
To eliminate the fraction, multiply both sides of the equation by the reciprocal of 2/5, which is 5/2:
(5/2)(2/5)x = (5/2)(-19/5)
Canceling out the common factors, you get:
(1)x = -19/2
Therefore, the solution to the equation (2/5)x + 4 = 1/5 is x = -19/2.
First, subtract 4 from both sides of the equation:
(2/5)x + 4 - 4 = 1/5 - 4
(2/5)x = 1/5 - 20/5
(2/5)x = -19/5
To eliminate the fraction, multiply both sides of the equation by the reciprocal of 2/5, which is 5/2:
(5/2)(2/5)x = (5/2)(-19/5)
Canceling out the common factors, you get:
(1)x = -19/2
Therefore, the solution to the equation (2/5)x + 4 = 1/5 is x = -19/2.
what is the solution to this equation 5/3 - 2x = 1/6
To find the solution of the equation 5/3 - 2x = 1/6, you need to isolate the variable x.
First, subtract 5/3 from both sides of the equation:
5/3 - 2x - 5/3 = 1/6 - 5/3
-2x = 1/6 - 5/3
To find a common denominator for the fractions, multiply the first fraction by 2/2 and the second fraction by 1/2:
-2x = (1/6)(2/2) - (5/3)(1/2)
-2x = 2/12 - 5/6
Next, combine the fractions:
-2x = 1/12 - 10/12
-2x = -9/12
To simplify the fraction, divide both the numerator and denominator by their greatest common divisor, which is 3:
-2x = (-9/3)(1/4)
-2x = -3/4
Finally, divide both sides of the equation by -2 to solve for x:
(-2x)/(-2) = (-3/4)/(-2)
x = 3/8
Therefore, the solution to the equation 5/3 - 2x = 1/6 is x = 3/8.
First, subtract 5/3 from both sides of the equation:
5/3 - 2x - 5/3 = 1/6 - 5/3
-2x = 1/6 - 5/3
To find a common denominator for the fractions, multiply the first fraction by 2/2 and the second fraction by 1/2:
-2x = (1/6)(2/2) - (5/3)(1/2)
-2x = 2/12 - 5/6
Next, combine the fractions:
-2x = 1/12 - 10/12
-2x = -9/12
To simplify the fraction, divide both the numerator and denominator by their greatest common divisor, which is 3:
-2x = (-9/3)(1/4)
-2x = -3/4
Finally, divide both sides of the equation by -2 to solve for x:
(-2x)/(-2) = (-3/4)/(-2)
x = 3/8
Therefore, the solution to the equation 5/3 - 2x = 1/6 is x = 3/8.
what is the solution of this equation 0.2x - 2.15 = -8.27
To find the solution of the equation 0.2x - 2.15 = -8.27, you need to isolate the variable x.
First, add 2.15 to both sides of the equation:
0.2x - 2.15 + 2.15 = -8.27 + 2.15
0.2x = -6.12
Next, divide both sides of the equation by 0.2 to solve for x:
(0.2x)/(0.2) = (-6.12)/(0.2)
x = -30.6
Therefore, the solution to the equation 0.2x - 2.15 = -8.27 is x = -30.6.
First, add 2.15 to both sides of the equation:
0.2x - 2.15 + 2.15 = -8.27 + 2.15
0.2x = -6.12
Next, divide both sides of the equation by 0.2 to solve for x:
(0.2x)/(0.2) = (-6.12)/(0.2)
x = -30.6
Therefore, the solution to the equation 0.2x - 2.15 = -8.27 is x = -30.6.